DAMPAK PENINGKATAN KONSUMSI KARET ALAM DOMESTIK TERHADAP KESEJAHTERAAN PETANI KARET INDONESIA - Linda Purwaningrat; Tanti Novianti; Saktyanu Kristyantoadi Dermoredjo (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2021)
Rubber is a people's commodity that contributes greatly to the Indonesian economy. However, the price of natural rubber fluctuates with a downward trend, thus affecting state income and the welfare of Indonesian rubber farmers. Therefore, the natural rubber-producing countries in the ITRC forum agreed to increase domestic natural rubber consumption in their respective countries as an effort to stabilize the price of rubber in the world. This policy was later referred to as the Demand Promotion Scheme (DPS). This study aims to see the impact of the application of DPS as a domestic natural rubber trade policy on the welfare of Indonesian rubber farmers. The analysis uses an econometric model in the form of a system of simultaneous equations which is estimated by the Two-Stage Least Squares (2SLS) method using the 1992–2017 annual data series. The results of this study indicate that the implementation of policies to increase domestic natural rubber consumption can improve the welfare of Indonesian rubber farmers.